2022
DOI: 10.1186/s13244-022-01256-x
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic CT and MRI features of primary parotid squamous cell carcinoma and its predictive factors for differential diagnosis with mucoepidermoid carcinoma

Abstract: Background Primary parotid squamous cell carcinoma (SCC) is a rare entity with a poor prognosis. Pathologically, the diagnosis of it requires the exclusion of parotid mucoepidermoid carcinoma (MEC). Currently, the imaging features of primary parotid SCC and the predictive indicators for differential diagnosis of the two entities have not been well reported. Our purpose was to identify the imaging characteristics of primary parotid SCC and to determine the predictive factors for its’ differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
3
1
Order By: Relevance
“…This is consistent with the studies of others, where smaller Sphericity is more likely to induce LNM in breast cancer and esophageal cancer [29]. In clinical practice, an important feature for radiologists to read CT to judge lung tumors is the burr-like structure [31], which also represents the irregularity of the tumor. Burr-like structure of NSCLC is more aggressive and has poor prognosis [32].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with the studies of others, where smaller Sphericity is more likely to induce LNM in breast cancer and esophageal cancer [29]. In clinical practice, an important feature for radiologists to read CT to judge lung tumors is the burr-like structure [31], which also represents the irregularity of the tumor. Burr-like structure of NSCLC is more aggressive and has poor prognosis [32].…”
Section: Discussionsupporting
confidence: 90%
“…Our study also confirmed this theory. And in our study RobustMeanAbsoluteDeviation has carried on the wavelet, exponential and square transformation makes the futertes of the multiple correction, and stronger stability [31]. Shen et al [28].…”
Section: Discussionmentioning
confidence: 78%
“…[12,13] Additionally, the degree of tumor enhancement after contrast administration did not signi cantly help differentiate benign from malignant tumors, although there was a tendency toward strong enhancement in benign tumors. [14] Similarly, our study did not nd statistical signi cance in the enhancement category. However, some authors have reported that tumor homogeneity correlates well with histologic ndings.…”
Section: Discussioncontrasting
confidence: 67%
“…It is efficient in verifying suspected malignancy and can provide extensive anatomical information regarding the primary tumor's location and its relationship to the FN and surrounding tissues [3,4]. In addition to the well-known signs of parotid malignancy, such as poorly defined borders, large tumor size with noticeable invasiveness, irregular shape, infiltration of extra-parotid lymph nodes, and low to moderate signal intensity on T2-weighted images, relatively large tumors with central necrosis is a useful imaging feature of SCC originating in the parotid gland (Figure 1) [5,6].…”
Section: Discussionmentioning
confidence: 99%